Japanese law - Oda, Hiroshi, 1952- (Oxford : Oxford University Press, 2009)
This text covers the entire range of Japanese law with an emphasis on commercial law covering such topics as the reform of the company law, internationalisation of competition law, the financial big bang, and cross-border litigation.
Previous ed.: 1999.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Japan; Law -- Japan -- History; Law